2021
DOI: 10.1093/g3journal/jkab141
|View full text |Cite
|
Sign up to set email alerts
|

Application of a bioinformatic pipeline to RNA-seq data identifies novel virus-like sequence in human blood

Abstract: Numerous reports have suggested that infectious agents could play a role in neurodegenerative diseases, but specific etiological agents have not been convincingly demonstrated. To search for candidate agents in an unbiased fashion, we have developed a bioinformatic pipeline that identifies microbial sequences in mammalian RNA-seq data, including sequences with no significant nucleotide similarity hits in GenBank. Effectiveness of the pipeline was tested using publicly available RNA-seq data and in a reconstruc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Notably, 18/20 of these genes were identified as differentially expressed between sALS patients and controls. The best‐performing classification model was applied to normalised gene expression counts derived from an independent ALS‐control whole blood RNA‐seq data set (n = 60) [ 39 ]. This resulted in an ALS‐control classification accuracy of 63.3% (sensitivity: 60.0%, specificity: 66.7%, AUC: 64.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, 18/20 of these genes were identified as differentially expressed between sALS patients and controls. The best‐performing classification model was applied to normalised gene expression counts derived from an independent ALS‐control whole blood RNA‐seq data set (n = 60) [ 39 ]. This resulted in an ALS‐control classification accuracy of 63.3% (sensitivity: 60.0%, specificity: 66.7%, AUC: 64.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Leave‐One‐Out (LOO) cross‐validation was used to evaluate the effectiveness of selected features in classification and regression models. Validation of the classification model was also tested on an independent whole blood RNA‐seq data set consisting of 30 ALS cases and 30 controls [ 39 ] (Figure S4 ). All machine learning was conducted in Python v3.8.2 [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, many previous studies have found evidence of infections caused by various viruses and bacteria, which motivated us to conduct metagenomic analysis using RNA-seq data. [46][47][48][49][50] The alpha diversity values were similar between COPD and normal tissues, but the normal tissue samples had diverse values of alpha diversity, indicating a wider but restricted range of microbiome communities. This suggests that COPD tissues may have a distinct microbiome community compared to normal tissues.…”
Section: Discussionmentioning
confidence: 97%
“…I note that analysis of human transcriptome data in my lab has also led to the recovery of long non-repetitive sequences that lack significant nucleotide matches in GenBank. 48 Further characterization of instances of DNA or RNA “dark matter” will be required to determine their biological relevance.…”
Section: A Dark Brain Microbiome?mentioning
confidence: 99%